THE UNEASY CASE FOR COPYRIGHT: A STUDY OF COPYRIGHT IN BOOKS PHOTOCOPIES, AND COMPUTER PROGRAMS - Breyer, Stephen (Harvard Law Review)
Congress is currently considering the first major revision of the Copyright Act of 1909. Professor Breyer examines the moral and economic rationale for copyright in books. He goes on to consider proposals that would lengthen the term of protection and increase its scope in relation to photocopies and computer programs. On the basis of existing evidence he is unable to conclude that copyright should be abolished, but he argues that its extension is unnecessary and would be harmful.